Examining an Islamic Financial Inclusivity and Its Impact on Fundamental Economic Variables in Indonesia (An Approach of Static Panel Data Analysis) - Andre Pupung Darmawan; Angga Erlando; Dwi Budi Santoso (Universitas Airlangga, 2023)
ABSTRACT Previous studies mostly measured sharia financial inclusion using an index consisting of three dimensions: accessibility, availability, and usage. This research develops it by adding a digitalization dimension so that there are 4 dimensions in measuring sharia financial inclusion in Indonesia using an index. The first objective of this study is to visually illustrate the results of calculating the sharia financial inclusion index (in map form) in 33 provinces in Indonesia, using GeoDa software. Second, analyze the impact of sharia financial inclusion variables (the 4 form dimensions) that are calculated, on economic fundamental variables (growth, unemployment, poverty, and inequality) through a quantitative approach based on panel data analysis methods (FEM and REM). The secondary data used comes from the Financial Services Authority (OJK) and the Central Statistics Agency (BPS), in the 2015-2020 period. The results of this study indicate that sharia financial inclusion in Indonesia needs to be increased more evenly, so that it is not stagnant and centered in Java or provinces with a communal Muslim base (viewed from the results of index calculations) because the values